Evaluation Program of the Appraisal List of Officers Personnel Assigned In the Indonesian Navy (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this research is to find out the effectiveness of the Program of "Appraisal List of Officers Personnel Assigned in the Indonesian Navy (Dapen Persmil TNI AL)" at the Office of the Navy Personnel Service, Jl. Cilangkap Jakarta. Officers’ assignments are not enough if they are not supported by the awareness of the leadership of the Navy to totally touch on human resources management, especially at Navy Officers and not merely a rhetoric. However, the implementation of the assignment of Navy officers experienced problems related to the attitude and behavior. Therefore, in reality the implementation of the program of Dapen Persmil is not in accordance with the career development program for the Navy personnel launched by the Armed Forces Commander in 2016 until 2017 in the Principal Commands of the TNI Commander’s policy on enhancing the professionalism of soldiers through assignment, education and training, fulfillment of equipment, and soldier rights are managed with a good management system. Based on scientific literature, this research is a evaluation program study and the evaluation model. Data obtained through observation instruments, interviews, and documentation as well as using descriptive survey research methods, by means of explanotary and qualitative approaches. On the basis of the principle of model development, the effectiveness of the program, it is hoped that Navy Officers assigned to the Navy will no longer cause problems in their assignments but can develop skills and professionalism in order to improve work optimization. Keywords: human resources management, the program of Dapen Persmil TNI AL, evaluation program, Indonesian National Navy